Changes in the influenza threat as a result of the modification of the structure of the influenza virus - Brydak, Lidia B. (Przewodnik Lekarza/Guide for GPs, 2010)
Influenza is a severe infectious disease of the respiratory tract caused by the influenza virus, where continuous evolution of the virus has a significant effect on the sequelae of the virus on the general population during seasonal epidemic outbreaks of influenza and also during the pandemics that occur. Two essential surveillance units, GISN and EISN, exist. They identified A/H5N1/ (HPAI), A/H7N7/(HPAI) or A/H1N1/v. On June 11th, 2009, the World Health Organization (WHO) announced a pandemic caused by the influenza virus A/H1N1/v. The virus is a quadruple reassortant virus. Up until January 15th, 2010, according to the WHO, as a result of the pandemic 13 554 victims succumbed to the virus. The only anti-viral drugs available are neuraminidase inhibitors oseltamivir and zanamivir.